2021
DOI: 10.1021/acssuschemeng.1c05757
|View full text |Cite
|
Sign up to set email alerts
|

Degradable Cross-Linked Collagen Fiber/MXene Composite Aerogels as a High-Performing Sensitive Pressure Sensor

Abstract: Degradable multifunctional pressure sensors have attracted considerable attention in recent years, owing to their unique sensing performance and potential in reducing electronic waste, for applications in monitoring human motion and medical detection and human−computer interactions. Herein, cross-linked collagen fibers (CCFs) and MXene are used to prepare CCF/MXene composite aerogels by blending-casting and freeze-drying. The CCF/ MXene composite aerogel sensor exhibits a high sensitivity (61.99 kPa −1 ), quic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 66 publications
0
30
0
Order By: Relevance
“…For instance, Geravand et al ( Abbasi Geravand et al, 2021 ) developed a novel biodegradable nano-filtration membrane using a hybrid nanocomposite fabricated from polycaprolactone (PLC) and Ti 3 C 2 (OH) 2 hydrophilic MXene sheets for the treatment of dyed aqueous solutions. Also, Zhang et al (W. Zhang et al, 2022 ) revealed an intriguing biodegradable multipurpose pressure sensor developed using cross-attached collagen fibres (CCFs) with MXene aerogel exhibiting a great sensitivity response of 61.99 kPa −1 within a short time of 0.30s, speedy recovery within few milliseconds of 0.15s, high thermal steadiness, and small LDL (0.4 kPa).…”
Section: Challenges Potential Solutions and Prospectsmentioning
confidence: 99%
“…For instance, Geravand et al ( Abbasi Geravand et al, 2021 ) developed a novel biodegradable nano-filtration membrane using a hybrid nanocomposite fabricated from polycaprolactone (PLC) and Ti 3 C 2 (OH) 2 hydrophilic MXene sheets for the treatment of dyed aqueous solutions. Also, Zhang et al (W. Zhang et al, 2022 ) revealed an intriguing biodegradable multipurpose pressure sensor developed using cross-attached collagen fibres (CCFs) with MXene aerogel exhibiting a great sensitivity response of 61.99 kPa −1 within a short time of 0.30s, speedy recovery within few milliseconds of 0.15s, high thermal steadiness, and small LDL (0.4 kPa).…”
Section: Challenges Potential Solutions and Prospectsmentioning
confidence: 99%
“…For instance, Zhang et al. [ 205 ] fabricated a pressure sensor utilizing cross‐linked collagen fibers and MXene aerogel. They showed the sensor degrades on soaking in an alkaline solution within forty days, indicating that the inclusion of natural fibers in the aerosol aid in biodegradability.…”
Section: Cutting‐edge Prospectsmentioning
confidence: 99%
“…Additionally, MXP HNC layers have also been employed as joule heaters for the selec tive and sensitive operation of chemiresistors based on other sensing materials. [203] MXP HNCs are also reported to be either biodegradable [204] or degradable [205] in specific solu tions, which reduces the probability of solidwaste generation due to the anticipated massive application of MXP HNCs. For instance, Zhang et al [205] fabricated a pressure sensor utilizing crosslinked collagen fibers and MXene aerogel.…”
Section: Cutting-edge Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…MXene dispersion and CCF suspension were prepared by the previously reported method. 37 MXene dispersion (1.83 g, 2.18 wt %) was added to 10.00 g of CCF suspension (0.75 wt %) and stirred for 30 min. Then, 0.104 g AgNPs was added to the CCF/MXene (CM) suspension and stirred for 30 min.…”
Section: ■ Introductionmentioning
confidence: 99%